Sistem Informasi Manajemen Persewaan Aset Karang Taruna Emblem Desa Kemiri Klaten - Wulan Nur Layli; Eko Purwanto; Nibras Fa’iq Muhammad (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
This study aims to develop a web-based asset rental management information system to address the issues of manual record-keeping still used by Karang Taruna Emblem in Kemiri Village. The research methods include observation, interviews, and literature review for data collection, as well as the Waterfall model approach for system development. The process involves requirements analysis, system design using Unified Modeling Language (UML), and implementation using the Laravel framework and MySQL database. The system is designed to support digital transaction processing for asset rental, returns, and scheduling, with two access roles: admin and renter. The implementation results indicate that the system improves operational efficiency, minimizes the risk of data loss, accelerates information retrieval, and provides automated and real-time transaction reporting. Based on Black Box testing, all system functions perform as expected. The system also assists administrators in monitoring asset inventory and rental activities, while providing the public with convenient online access to asset information. Therefore, this information system enhances data accuracy, service transparency, and the professionalism of asset management within the Karang Taruna organization.